Enhancing Water Resource Management Efficiency through Smart Technologies: A Case Study in Kashkadarya Region, Uzbekistan: Meningkatkan Efisiensi Pengelolaan Sumber Daya Air melalui Teknologi Cerdas: Studi Kasus di Wilayah Kashkadarya, Uzbekistan - Meyli Kizi, Abduhalimova Nafisa (Universitas Muhammadiyah Sidoarjo, 2023)
This article presents a comprehensive study on the implementation of